2020
DOI: 10.21203/rs.3.rs-78801/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Baseline Serum Total Cortisol During the Primary Corona Virus Infection in the Beginning of the Pandemic in Cameroon

Abstract: Introduction: Improvement of critically ill patients Covid 19 positive placed on glucocorticoids may suggest impairment of the adrenal function. Our objective was to evaluate baseline serum cortisol in covid+ patients.Methods: This was a descriptive and analytical cross-sectional study conducted in a population of patients infected with 2019-nCoV in Cameroon. Patients receiving corticosteroids irrespective of the route of administration within 3 months prior to recruitment and those with any hypothalamic-pitui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 8 publications
1
9
0
Order By: Relevance
“…Further in line with our findings, patients with COVID-19 also showed significant sex-based differences in cortisol levels ( Etoga et al. 2021 ), which is consistent with previous results that cortisol responses to stress were higher in males compared with females ( Kirschbaum et al.…”
Section: Discussionsupporting
confidence: 93%
“…Further in line with our findings, patients with COVID-19 also showed significant sex-based differences in cortisol levels ( Etoga et al. 2021 ), which is consistent with previous results that cortisol responses to stress were higher in males compared with females ( Kirschbaum et al.…”
Section: Discussionsupporting
confidence: 93%
“…; (6) Was the post-intervention clinical condition clearly described? ; (7) Were adverse events (harms) or unanticipated events identified and described? ; (8) Does the case report provide takeaway lessons?…”
Section: Data Extraction Process and Assessment For Study Qualitymentioning
confidence: 99%
“…6 However, in about 30%-70% of sepsis cases, the adrenal reaction is insufficient or there is glucocorticoid periphery resistance, all of which are linked to a weak prognosis and necessary supplementation. 7…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Like us, they concluded that the absence of a marked rise of cortisol during COVID-19 suggests the possible involvement of the hypothalamic-pituitary-adrenal axis in this infection. However, their study did not have a non-COVID control group (28).…”
Section: Biochemical and Laboratory Evaluationsmentioning
confidence: 98%